The Hydrophobic Effect Contributes to the Closed State of a Simplified Ion Channel through a Conserved Hydrophobic Patch at the Pore-Helix Crossing - Yonkunas, Michael; Kurnikova, Maria (Frontiers in Pharmacology, 2015)
Ion selectivity-filter structures are strikingly similar throughout the large family of K+ channels and other p-loop-like receptors (i.e., glutamate receptors). At the same time, the triggers for opening these channels, or gating, are diverse. Two questions that remain unanswered regarding these channels are: 1) what force(s) stabilize the closed non-conducting channel-pore conformation? And 2) what is the free energy associated with transitioning from a closed (non-conducting) to an open (conducting) channel-pore conformation? The effects of charge and hydrophobicity on the conformational states of a model tetrameric biological ion channel are shown utilizing the amino acid sequence from the K+ channel KcsA as the model “channel”. Its widely conserved hydrophobic bundle crossing located adjacent to the lipid head-groups at the intracellular side of the membrane was calculated to have a 5 kcal/mol free energy difference between modeled open and closed conformations. Simulated mutants of amino acids within the hydrophobic region significantly contribute to the size of this difference. Specifically for KcsA, these residues are part of the pH sensor important for channel gating and our results are in agreement with published electrophysiology data. Our simulations support the idea that the hydrophobic effect contributes significantly to the stability of the closed conformation in tetrameric ion channels with a hydrophobic bundle crossing positioned in proximity to the lipid head groups of the biological membrane.